2020
DOI: 10.37441/cejer/2020/2/1/5759
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Characteristics of Helping Professionals

Abstract: In Hungary, considerable efforts have been made in recent years to analyse the career paths of higher educational graduates, which have highlighted the need for field-specific and training-specific analysis. In this context, our research concentrates on a special training segment, focusing on the position of young professionals working in occupations helping the function of the society. Previous research focused only on the professionalization of the different occupations and the recruitment was examined from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, during the survey of their academic history, former students also reflected upon their professional training, so experiences during formal education were not left out either. When analyzing the quantitative official longitudinal career data, it became clear to us that several elements of the professional socialization process were not examined in this type of research (Csók 2020). That is why we conducted the research based on a qualitative paradigm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, during the survey of their academic history, former students also reflected upon their professional training, so experiences during formal education were not left out either. When analyzing the quantitative official longitudinal career data, it became clear to us that several elements of the professional socialization process were not examined in this type of research (Csók 2020). That is why we conducted the research based on a qualitative paradigm.…”
Section: Methodsmentioning
confidence: 99%
“…A study of the career paths of young helping professionals in the fields of social work and education concluded that, whereas education graduates took a longer time to find a job and not all of them were able to find one matching their qualifications, social workers were less likely to leave their professions. Although education graduates had less favorable results regarding horizontal and vertical congruence (Csók 2020), social workers were also affected by income disadvantages (Benkő 2009;Csók 2020).…”
Section: Professional Socialization Of Trainees In Helping Professionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an explanation, families who are higher up the income and hierarchy ladder want their children to be able to reproduce at least their social status. Consequently, careers offering lower-income and prestige are less attractive to children of more highly qualified parents (Benkő, 2009;Csók, 2020). Data on parents' educational attainment suggest a more open nature of the fields of education in the lower tercile (e.g.…”
Section: Social Status Of Studentsmentioning
confidence: 99%
“…After two decades, the impact of location in the vertical hierarchy of society on schooling and degree attainment remains at the forefront of research (Pusztai, 2015a). Students are not a homogeneous group at entry (Csók et al, 2019;Kovács et al, 2019), which is based on the fact that they start their tertiary education under unequal conditions. The family and secondary school pathways of disadvantaged students are in many ways inferior to those of their peers in higher status (e.g.…”
Section: Introduction Economics Versus the Dual Value Of Higher Educa...mentioning
confidence: 99%